2021
DOI: 10.1002/jlcr.3925
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐mediated radioiodination reaction through aryl boronic acid or ester precursor and its application to direct radiolabeling of a cyclic peptide

Abstract: A copper‐mediated radioiodination using aryl boronic precursors is attracting attention as a solution to oxidative iododestannylation and nickel‐mediated radioiodination drawbacks. The copper‐mediated radiolabeling method allows radioiodination at room temperature with stable aryl boronic precursors without preparing complex starting materials or reagents and can be performed in a reaction vessel exposed to air. This method has good potential in radiochemistry; however, studies on the scope of copper‐mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…A copper-mediated radiolabeling reaction using a boronic precursor is well tolerated at the tracer level in both electron-rich and electron-poor substrates, including sterically crowded substrates. , However, in this study, using a mixture of solvents containing H 2 O/MeOH resulted in differences between positional isomers. These observations prompted us to investigate the effect of the substituents on labeling efficiency at the tracer level in a mixture solvent containing H 2 O/MeOH.…”
Section: Results and Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…A copper-mediated radiolabeling reaction using a boronic precursor is well tolerated at the tracer level in both electron-rich and electron-poor substrates, including sterically crowded substrates. , However, in this study, using a mixture of solvents containing H 2 O/MeOH resulted in differences between positional isomers. These observations prompted us to investigate the effect of the substituents on labeling efficiency at the tracer level in a mixture solvent containing H 2 O/MeOH.…”
Section: Results and Discussionmentioning
confidence: 65%
“…The target compounds ([ 125 I] 2 and [ 125 I] 4 ) were synthesized as shown in Figure . The radiolabeling protocol was prepared according to previously reported methods with some modifications. In this study, Cu­(py) 4 (OTf) 2 (py = pyridine, OTf = trifluoromethanesulfonate) was used as it was reported as the optimal copper catalyst for this labeling reaction . A boronic precursor ( 1 or 3 ) and Cu­(py) 4 (OTf) 2 dissolved in a solvent, water (H 2 O), or an organic solvent to control the H 2 O content of the reaction solvent were added to a microtube in this precise order.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kondo et al reported an efficient methodology for the direct radiolabeling of a peptide side chain via copper-mediated radioiodination by using an aryl boronic acid precursor through a Chan–Evans–Lam cross-coupling reaction ( Figure 14 D) [ 85 ]. This approach allows for the avoidance of heavy metals, heating, oxidizing reagents, an inert condition, as well as the preparation of complex starting materials.…”
Section: Boronic Acid-mediated Peptide Synthesis and Modificationsmentioning
confidence: 99%
“…This approach allows for the avoidance of heavy metals, heating, oxidizing reagents, an inert condition, as well as the preparation of complex starting materials. In addition, it can be carried out at room temperature, and is easily separated due to the significantly different polarity between the boronic acid precursor and the iodine compound [ 85 ].…”
Section: Boronic Acid-mediated Peptide Synthesis and Modificationsmentioning
confidence: 99%